2021
DOI: 10.1097/ee9.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sensitive windows of airborne lead exposure associated with behavioral outcomes at age 12

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…A similar study was conducted in one local area of India of school-age children constantly exposed to lead. The authors of this study reported elevated BLLs, which were far above the recommended standard in these children compared to other children [ 52 ].…”
Section: Lead Exposure: Low- and Middle-income Countries Versus High-...mentioning
confidence: 79%
See 1 more Smart Citation
“…A similar study was conducted in one local area of India of school-age children constantly exposed to lead. The authors of this study reported elevated BLLs, which were far above the recommended standard in these children compared to other children [ 52 ].…”
Section: Lead Exposure: Low- and Middle-income Countries Versus High-...mentioning
confidence: 79%
“…Rasnick et al [ 52 ] studied the health effects of lead exposure on 263 children. They found out that exposure to lead from the air was responsible for different health and behavioral problems such as increased anxiety, aggression and attention problems observed among these children.…”
Section: Introductionmentioning
confidence: 99%
“…Eight longitudinal, and 6 cross-sectional studies from Lithuania, China, Korea, Iran, Canada, USA, and the UK (n=45,607) explored the influence of air particulate matter on behavioural outcomes in typically developing children [27,100,109,110,119,130,131,133,136,137,[139][140][141][142][143]. One study was rated as high RoB [140], one as unclear RoB [131], and the remaining as low RoB.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Another study by Loftus et al, 2020 [139] explored the influence of exposure to particulate matter less than 10 microns (PM10) on parent reported child aggressive behaviours but it did not show a significant association (Very Low quality). Ambient air lead exposure (PbA) ) was associated with high parent-reported externalising behaviour ( [142], Very Low quality).…”
Section: Air Pollutionmentioning
confidence: 99%
“…Even within the developmental literature, there are mixed results: some studies suggest prenatal through adolescent exposure is linked to more internalizing problems (Margolis et al, 2016;Brokamp et al, 2019;Brunst et al, 2019;B. Fan et al, 2019;Rasnick et al, 2021;Yolton et al, 2019), where others have failed to find an association (Jorcano et al, 2019;Zhao et al, 2019). One potential limitation of many of these studies is a large age range over which links between exposure and mental health are assessed, which may fail to capture age-specific or nonlinear effects.…”
Section: Introductionmentioning
confidence: 99%